GAMBARAN KEMAMPUAN INTERAKSI SOSIAL PASIEN ISOLASI SOSIAL SETELAH PEMBERIAN SOCIAL SKILLS THERAPY DI RUMAH SAKIT JIWA - Sukma Ayu Candra Kirana (Jurnal Ilmiah Kesehatan, 2018)
Social isolation is one of the nursing diagnoses that can be established in patients who are symptomatic to withdraw, withdraw from social activities and do not want to interact with others even with nurses. Negative symptoms such as social isolation that can not be overcome can cause the client to experience positive symptoms and worsen her condition. One way to improve the interaction of patients with social isolation is to use Social Skills Therapy. The purpose of this research is to know the description of change of interaction ability of social isolation patient after given Social Skills Therapy. The method used was descriptive with 40 respondents of social isolation who were treated in one of the RSJ inpatient rooms in West Java, Indonesia. The result of this research is an increase of social interaction ability after given Social Skills Therapy. Therefore Social Skills Therapy can be recommended as one of the specialist therapies in providing nursing care in patients with social isolation.